2013
DOI: 10.1128/jvi.03142-12
|View full text |Cite
|
Sign up to set email alerts
|

Venezuelan Equine Encephalitis Virus nsP2 Protein Regulates Packaging of the Viral Genome into Infectious Virions

Abstract: Alphaviruses are one of the most geographically widespread and yet often neglected group of human and animal pathogens. They are capable of replicating in a wide variety of cells of both vertebrate and insect origin and are widely used for the expression of heterologous genetic information both in vivo and in vitro. In spite of their use in a range of research applications and their recognition as a public health threat, the biology of alphaviruses is insufficiently understood. In this study, we examined the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 46 publications
(50 reference statements)
1
37
0
Order By: Relevance
“…In the case of VEEV, it was demonstrated to function as a nuclear export signal (NES) playing a critical role in inhibition of nuclear pore trafficking (36,37). In a recent study, we also showed that in VEEV capsid, SD2 was capable of accumulating adaptive mutations (35). These mutations increased the efficiency of VEEV genome packaging by capsid protein mutants by a few orders of magnitude and compensated, to some degree, for the decrease in the capsid's positive charge in these mutants.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…In the case of VEEV, it was demonstrated to function as a nuclear export signal (NES) playing a critical role in inhibition of nuclear pore trafficking (36,37). In a recent study, we also showed that in VEEV capsid, SD2 was capable of accumulating adaptive mutations (35). These mutations increased the efficiency of VEEV genome packaging by capsid protein mutants by a few orders of magnitude and compensated, to some degree, for the decrease in the capsid's positive charge in these mutants.…”
Section: Resultsmentioning
confidence: 87%
“…These mutations increased the efficiency of VEEV genome packaging by capsid protein mutants by a few orders of magnitude and compensated, to some degree, for the decrease in the capsid's positive charge in these mutants. These adaptive mutations did not generate additional positive charge and functioned synergistically with adaptive mutations accumulating in VEEV nsP2 protein (35). (iii) SD3 (aa 52 to 110) is a highly positively charged subdomain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations